2014
DOI: 10.1080/01490400.2014.885857
|View full text |Cite
|
Sign up to set email alerts
|

Testing a Structural Model of Psychological Well-Being and Constraints Negotiation in Recreational Sports Participation in Individuals with Type 2 Diabetes

Abstract: The relationships among psychological well-being, constraints, negotiation, and participation were examined using structural equation modeling in patients with type 2 diabetes using a cross-sectional survey approach (N = 283). Despite a direct negative effect of constraints and a positive effect of negotiation on participation in recreational sports, we found no significant effect of constraints on the negotiation efforts of respondents. Instead, psychological well-being played an important role in the process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 59 publications
(128 reference statements)
2
6
0
Order By: Relevance
“…Instead, negotiation independently influences participation. This is consistent with Ma and Ma (2014), Wilhelm Stanis et al (2009), and Son et al (2008), suggesting that the strategies and resources used by the respondents were facilitators rather than negotiators. However, the results are inconsistent with previous studies that found negative relationships between constraint and participation (Chen, 2012;Hung et al, 2013;Kim & Trail, 2010;Son et al, 2008;White, 2008) and positive relationships between constraint and negotiation (Chen et al, 2018;Hubbard & Mannell, 2001;Loucks-Atkinson & Mannell, 2007;White, 2008).…”
Section: Constraints-effects-mitigation Modelsupporting
confidence: 86%
See 2 more Smart Citations
“…Instead, negotiation independently influences participation. This is consistent with Ma and Ma (2014), Wilhelm Stanis et al (2009), and Son et al (2008), suggesting that the strategies and resources used by the respondents were facilitators rather than negotiators. However, the results are inconsistent with previous studies that found negative relationships between constraint and participation (Chen, 2012;Hung et al, 2013;Kim & Trail, 2010;Son et al, 2008;White, 2008) and positive relationships between constraint and negotiation (Chen et al, 2018;Hubbard & Mannell, 2001;Loucks-Atkinson & Mannell, 2007;White, 2008).…”
Section: Constraints-effects-mitigation Modelsupporting
confidence: 86%
“…The current study found that constraint did not significantly influence participation (Wilhelm Stanis et al, 2009;Chen et al, 2018) or negotiation (Ma & Ma, 2014;Son et al, 2008;Wilhelm Stanis et al, 2009). The current findings did not support the constraints-effectsmitigation model that negotiation mediated the relationship between constraint and participation (Hubbard & Mannell, 2001).…”
Section: Constraints-effects-mitigation Modelmentioning
confidence: 43%
See 1 more Smart Citation
“…CNT has an extensive history of theorisation, modelling, and construct development, especially within the field of leisure studies to understand factors affecting leisure participation and the extent to which they can be negotiated (Crawford et al, 1991;Hawkins et al, 1999;Jackson et al, 1993). A growing body of literature has expanded beyond the field of leisure studies including to disability studies (Burns & Graefe, 2007;Crawford & Stodolska, 2008;Henderson et al, 1995;Loucks-Atkinson & Mannell, 2007;Lyu et al, 2013;Ma & Ma, 2014;McKercher & Darcy, 2018;Park & Chowdhury, 2018).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…It should also be noted that many empirical studies have been conducted in academia to identify the factors that affect participation in leisure activities. Amongst these factors, the relationship between participation in leisure activities was observed in terms of leisure constraints, leisure motivation, self-efficacy, leisure attitude, subjective norms, perceived behavioral control, aspiration, and leisure constraint negotiation variables ( Alexandris et al, 2007 ; Son et al, 2008 ; Kim, 2009 ; Lee and Scott, 2009 ; Choi et al, 2011 ; Hung and Petrick, 2012 ; Ryu and Lee, 2012 ; Ma and Ma, 2014 ; Son and Kim, 2014 ; Moghimehfar et al, 2018 ; Lee, 2019 ; Lim and Lee, 2019 ). In particular, leisure constraint negotiations have consistently been reported to be one of the major determinants of participation in leisure activities.…”
Section: Introductionmentioning
confidence: 99%